Online Shopping Behavior of Students in Select Asian Countries (India, Malaysia, Singapore, Uzbekistan and Thailand) - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Electronic Commerce has become one of the essential characteristics in the internet era. Online shopping has become the third most popular internet activity, immediately following e-mail usage/ instant messaging and web browsing (Puranik & Bansal, 2014). E-commerce is the purchase and sale of goods and/or services via electronic channels like the internet (businessnewsdaily.com, 2015). One of the oldest studies was done by Quelch and Takeuchi (1981) who have touched some of the factors to understand the online shopping behavior of consumers. It is predicted that such users may take time to feel at ease in the use of technology and the younger generation would adopt it earlier. Online purchasing decisions have mainly concentrated on identifying the factors which affect the willingness of consumers to engage in internet shopping. Schiffman et al. (2001); Jarvenpaa and Todd (1997) have proposed a model of attitudes and shopping intention towards internet shopping in general.